Escorting Democracy with Local Wisdom: Depiction of Regional Election Supervision in the midst of Pandemic - Kristian Kristian; Nuraliah Ali; Karlinae D Bangas; Supiya Supiya (Universitas Medan Area, 2021)
This paper aims to describe the supervision of the Central Kalimantan regional head election during the pandemic. The problem is focused on how the description of election supervision by Election Supervisory Agency? and what constraint are faced and their solutions in the context of local wisdom?. The research type is descriptive qualitative. Data Collecting through interviews, observation, and literature study. The data obtained were analyzed descriptively using the Mile and Huberman model. This study shows several things: First, the implementation of supervision is more on tasks outside the crucial task of Bawaslu, namely the supervision of the pandemic health protocols as an additional task burden. Second, the obstacles faced by Bawaslu starting from the preparation, voting, and post-voting. Namely: Updating and determining the voter list was constrained by the Work From Home and Large-Scale Social Restrictions policies; Procurement and distribution of logistics whose suppliers had not yet recovered from the impact of the pandemic; Some officials were reluctant and resigned because of the rapid test rules; distorted ballot papers; The officers' lack of compliance with the working mechanism that had been determined. Third, The context of local wisdom in the supervision of Pilkada in Central Kalimantan, namely: Balanga, Huma Betang, Ma'mapas Lewu, Isen mulang, and Dayak Greetings: Tabe salamat lingu nalatai, Salam Sujud Karendem malempang, Adil ka’ Talino bacura’mi ka’ Saruga, Basengat kajubata.